Is MRSA screening in obstetrics a waste of time and resource?. (18th April 2012) - Adams, EW; Cooper, J; Rowlands, D; Bricker, L
Abstract : Background: MRSA colonisation is a risk factor for MRSA infection. In the current drive for economies, we examined MRSA screening as a potential cost-saving area. Methods: All trusts in the Northwest SHA region provided details of their MRSA screening policy and rates of MRSA colonisation, MRSA bacteraemia, neonatal infection with MRSA and their Trust's MRSA bacteraemia rate. These results were compared with standard national maternity data. Results: Maternity units representing 53% of deliveries in the Northwest, covering secondary and tertiary units returned data. The policies detailing how MRSA screening should be undertaken showed wide variation. The prevalence of MRSA colonisation in pregnant women screened in maternity units was 0.178%. Across the Northwest, there was 1 case of maternal MRSA bacteraemia. Discussion: The UK patient MRSA colonisation prevalence is estimated at 7.5%. Pregnant women are low risk as they are under 65, are generally admitted from home (rather than care homes) and are female. These different groups all have a lower prevalence than the average patient. The clinical usefulness of screening pregnant women for MRSA colonisation particularly in the current economic climate is questionable. The region spent approximately £67, 000 simply on screening tests in 2009. However, we did not collect data on bacteraemia in this population prior to introducing a screening policy, so it is unclear whether the low bacteraemia rate is as a result of successful decolonisation or would be low anyway. We would recommend a cluster randomised trial to look at whether pregnant women should be screened for MRSA.